Metadata Analysis of mcr-1-Bearing Plasmids Inspired by the Sequencing Evidence for Horizontal Transfer of Antibiotic Resistance Genes Between Polluted River and Wild Birds - Lin, Yufei; Dong, Xiaohong; Wu, Jiao; Rao, Dawei; Zhang, Lihua; Faraj, Yousef; Yang, Kun (Frontiers in Microbiology, 2020)
We sequenced the whole genomes of three mcr-1-positive multidrug-resistant E. coli strains, which were previously isolated from the environment of egret habitat (polluted river) and egret feces. The results exhibit high correlation between antibiotic-resistant phenotype and genotype among the three strains. Most of the mobilized antibiotic resistance genes (ARGs) are distributed on plasmids in the forms of transposons or integrons. Multidrug-resistant (MDR) regions of high homology are detected on plasmids of different E. coli isolates. Therefore, horizontal transfer of resistance genes has facilitated the transmission of antibiotic resistance between the environmental and avian bacteria, and the transfer of ARGs have involved multiple embedded genetic levels (transposons, integrons, plasmids and bacterial lineages). Inspired by this, systematic metadata analysis was performed for the available sequences of mcr-1-bearing plasmids. Among these plasmids, IncHI2 plasmids carry the most additional ARGs. The composition of these additional ARGs varies according to their geographical distribution. The phylogenetic reconstruction of IncI2 and IncX4 plasmids provides the evidence for their multiregional evolution. Phylogenetic analysis at the level of mobile genetic element (plasmid) provides important epidemiological information for the global dissemination of mcr-1 gene. Highly homologous mcr-1-bearing IncI2 plasmids have been isolated from different regions along the East Asian-Australasian Flyway, suggesting that migratory birds may mediate the intercontinental transportation of ARGs.